SOFTWARE AS ART. - Bond, Gregory W. (Communications of the ACM, 2005)
This article focuses on the interplay between computer software and fine art. Compared to other artistic media, software has a very short history. Casting software as an artistic medium might strike many people as odd, or even objectionable, but there is a growing body of evidence to show that it is perceived and utilized in just this way. Programmers passionate about their work may sense an aesthetic that underlies their approach to software development and provides them with visceral feedback at every stage of development. In the past four years new-media art festivals have presented awards for artistic software and art museums have featured software in exhibitions. The renowned computer scientist Donald Knuth has expounded on the art inherent in both programming and the program since the 1970s. As the sole developer of a number of large software projects, notably the still-popular TeX typesetting program, he has developed a refined sense of software aesthetics. As a professor at Stanford University, he also has had ample opportunity to subjectively assess the work of his students.